Developing Students’ Character and English Proficiency through News Item Text Learning - Akromah, Mufidatul; Susanto, Dias Andris; Sukmaningrum, Rahmawati (Universitas PGRI Semarang, 2022)
Success in teaching and learning English is closely tied to the development of positive student character. Strong character traits help students harness their talents and build the resilience and self-confidence needed to face challenges and compete beyond the school environment. This study focused on the tenth-grade students of SMAN 1 Pemalang whose English proficiency was initially below the Minimum Competency Standard of 75. Pre-test results showed that 9 students (28.12%) did not meet the standard. After implementing character-based learning strategies, post-test results indicated significant improvement, with only 2 students (6.25%) falling short of the standard. The average score increased by 10.66 points, from 75.97 to 86.63. The integration of character-building activities fostered positive traits such as helpfulness, cooperation, care, confidence, sportsmanship, mutual respect, and high motivation. Feedback from questionnaires and interviews revealed that students felt more comfortable and happier in class, viewing it as a supportive and inclusive community. They learned in a relaxed environment, developed positive attitudes, and engaged in healthy, respectful competition. Ultimately, the cultivation of good character contributed significantly to their academic success.